IMPLEMENTASI KURIKULUM MERDEKA DALAM PENGELOLAAN KELOMPOK BERMAIN DENGAN ANALISIS SWOT - Asayyidatina Ramadianty, Ashil; Musa, Safuri; Muis, Abdul (IKIP Siliwangi, 2024)
The background of this research is the government policy regarding the independent curriculum. The results of studies on the implementation of the independent curriculum show positive and significant changes in the development of learning for students. As what has been done by who year brp. With regard to that, the purpose of this study is to conduct a swot analysis of the planning, organization, implementation, and supervision of the Aditya Karawang playgroup. Implementation of the independent curriculum in play groups in this case is a case study of the aditya play group. The theories used in this research are the independent curriculum according to Wasis, management according to D.Sudjana, playgroups according to the Ministry of Education, swot analysis according to Siagian. This research method uses descriptive qualitative with four research subjects, namely one manager, two tutors, and one parent of students. Based on the results in the field, it was found that the implementation of an independent curriculum in planning, organizing implementation, and supervision. The conclusion of the results of this study is to describe the implementation of the playgroup curriculum running well and smoothly but there are obstacles with limited electronic devices, learning media, control capabilities. The recommendations for the implementation of the independent curriculum in playgroups have not been maximized due to limited communication technology tools, teachers have not participated in med development training.